The clinical and molecular spectrum of AGO2-associated Lessel-Kreienkamp neurodevelopmental syndrome - Debora Tibbe; Christina Kiel; Olena Ielesicheva; Kerstin Robles de Maruri; Helia Mahboobi; Joschka Züghart; Hans-Hinrich Hönck; Christoph Meier; Fabiola Biasella; Marcela Legüe; María Francisca Lopez Avaria; Edward Blair; et al. (Genome Medicine, 2026)
Abstract Background Pathogenic variants in AGO2 , encoding a central component of the RNA-induced silencing complex (RISC), cause the neurodevelopmental disorder Lessel-Kreienkamp syndrome (LESKRES). The variant spectrum and associated molecular mechanisms underlying phenotypic variability and disease severity remain incompletely understood. Methods We investigated 45 newly identified individuals carrying 33 distinct AGO2 variants, 30 of which were previously unreported. Phenotypic data from these and previously reported cases ( n = 70) were integrated to delineate the LESKRES-associated clinical spectrum and genotype–phenotype correlations. Functional studies included shRNA-based silencing, co-immunoprecipitation, subcellular localization, and sequencing of AGO2-bound miRNAs. Results All individuals presented with a neurodevelopmental disorder of variable severity. Delayed speech and language development (97%), intellectual disability (97%), and motor delay (93%) were the most consistent features, frequently accompanied by muscular hypotonia, autistic traits, attention deficit hyperactivity disorder, visual impairment and structural brain anomalies. Systemic manifestations, including skeletal, craniofacial, cardiac, and male urogenital anomalies were common, underscoring AGO2’s multisystemic role. Moreover, we report occurrence of gonadal mosaicism and reveal the presence of interfamilial and variant-specific clinical heterogeneity. Variants clustered in defined regions of AGO2, including the L1 loop, helix-7, and multiple loops of the PIWI domain, highlight structural hotspots critical for RISC activity. Not all pathogenic variants impaired shRNA-mediated silencing; this was restricted to p.(Arg714Trp) and p.(Asn729His). Biochemical analyses revealed that p.(Asp619Asn) impaired GW182 binding and P-body assembly. Variants p.(Arg506Gln), p.(Glu531Gln) p.(Gly604Arg) and p.(Asp619Asn), reduced C-terminal phosphorylation, implicating defective AGO2 recycling. AGO2–miRNA co-immunoprecipitation and sequencing demonstrated variant-specific perturbations in miRNA association, strand selectivity, and isomiR generation. Variants near the hinge of the helix-7 region, especially p.(Phe182del), induced extensive changes in miRNA association and 3′-end modification, suggesting impaired anchoring within the miRNA-binding pocket. Conclusions Our findings substantially broaden the clinical and molecular landscape of LESKRES, establishing AGO2 as a pivotal regulator of neurodevelopment whose structural integrity is essential for precise miRNA-mediated gene regulation. Pathogenic variants disrupt distinct interconnected processes: P-body association, phosphorylation-dependent turnover, and miRNA interactions, culminating in dysregulated post-transcriptional gene silencing. These mechanistic insights link specific structural perturbations in AGO2 to graded clinical outcomes and underscore the critical role of AGO2 conformational dynamics in human neurodevelopment.